Phytochemical analysis, antioxidant, and antibacterial properties of partition fractions of Adansonia digitata and Annona muricata extracts using chloroform, ethyl acetate, ethanol, and aqueous solvent systems - Fagbohun Oyenike Bushirat; Hassan Abdusalam Adewuyi; Sakariyau Waheed Adio; Maryam Nana Musa; Timothy God-Giveth Olusegun; Ayomide Babatunde Ishola; Agumage Idoko; Adeola Victor Kolawole; Adesanmi Adefunmilayo Oluwatuyi; Sarah Ngozi Agwasim (Journal of Biomedical & Clinical Research, 2025)
Adansonia digitata and Annona muricata are traditionally used medicinal plants with reported pharmacological properties. In this study, we aimed to elucidate the phytochemical composition, antioxidant activity, and antibacterial properties of partition fractions of Adansonia digitata and Annona muricata extracts obtained using chloroform, ethyl acetate, ethanol, and aqueous solvent systems. The plant extracts were successively partitioned using chloroform, ethyl acetate, ethanol, and aqueous solvent systems. Phytochemical analysis was performed using standard methods. Antioxidant activity was evaluated using FRAP and DPPH assays. Antibacterial activity was assessed using agar well diffusion and MIC determination. Phytochemical analysis revealed the presence of alkaloids (10.2-15.6%), flavonoids (8.5-12.1%), and phenolic acids (5.6-9.2%) in all fractions. The ethyl acetate fraction of Annona muricata exhibited the highest antioxidant activity (IC50 = 20.5 μg/mL) in the DPPH assay, while the chloroform fraction of Adansonia digitata showed significant antioxidant activity (IC50 = 35.2 μg/mL) in the FRAP assay. The antibacterial evaluation demonstrated that the chloroform fraction of Adansonia digitata exhibited broad-spectrum antibacterial activity (MIC = 0.5-1.5 mg/mL) against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, whereas the ethyl acetate fraction of Annona muricata showed potent antibacterial activity (MIC = 0.25-1.0 mg/mL) against Gram-negative bacteria. Additionally, the ethanol fraction of Adansonia digitata displayed moderate antibacterial activity (MIC = 1.0-2.5 mg/mL) against Gram-positive bacteria, and the aqueous fraction of Annona muricata exhibited weak antibacterial activity (MIC = 2.5-5.0 mg/mL) against all tested bacterial strains. Comparison of antioxidant and antibacterial activities among fractions revealed significant variations, indicating the importance of solvent selection in extracting bioactive compounds. The study validates the traditional use of Adansonia digitata and Annona muricata, highlighting their potential as natural antioxidants and antibacterial agents.